On the Front Lines in "The Army of Peace": The Life and Witness of Ben Salmon to a Church and a World at War. (April 2017) - Baxter, Michael
Abstract : Ben Salmon was one of the four Catholic conscientious objectors during World War I. This article tells the story of his early commitment to justice for workers, his refusal to comply with conscription, and his arrest and incarceration in military prisons (part 1); contrasts Ben Salmon's story with the typical Catholic support for the war (part 2); presents an exposition of his thought on the basis of a lengthy statement of conscience that he wrote just before his release from military custody in November 1920 (part 3); and then reflects on the significance of his witness and words for inaugurating a counter‐tradition of a radical pacifism stance that has been taken up by later figures, such as Dorothy Day, Gordon Zahn, and Daniel Berrigan (part 4).